Growth Promoting Effect of Endophytic Bacteria Bacillus subtilis From Leaves of Vanda cristata and Its Potential Impact on In vitro Growth of Orchid - Chand, Krishna; Shah, Sujit; Pant, Bijaya (Journal of Nepal Biotechnology Association, 2023)
The orchids are well known for their microbial association. Bacillus subtilis has great diversity in Vanda cristata which is regarded as a potential growth enhancer for the development of plants. The isolation of its strain was confirmed as Bacillus subtilis by morphological and molecular sequencing of DNA. The isolate was tested for indole acetic acid (IAA) estimation, ammonia production and phosphate solubilization in qualitative and quantitative manners. Its growth-promoting activities were tested on in vitro-raised plantlets of Cymbidium aloifolium. B. subtilis synthesized the IAA with and without a precursor (tryptophan). A more amount of auxin was found by using more amount of tryptophan. During the qualitative test for ammonia and phosphate solubilization, both compounds were synthesized by B. subtilis, which was further confirmed by the quantification method. Further, B. subtilis was used as a biotic elicitor in the in-vitro mass propagation of C. aloifolium. The development of root and shoot was found significant in the tryptophan-treated elicitor than the other compared medium combination. This study concludes that B. subtilis can be used as a biological elicitor to promote the in vitro growth of C. aloifolium and puts the spectrum on microbial relationships with orchid species.